An Assessment of the Employee Job Satisfaction: Views from Empirical Perspectives - Agbenyegah, Albert Tchey (Journal of Economics and Behavioral Studies, 2019)
Job satisfaction stresses on the personal feelings within the job environment in relation to job assessment. Various academics and scientists studied in the past, the significant association between personal expectations and job satisfaction of employees. These past studies were based on the model of personality traits and other variables in determination of employee job satisfaction. This study is to assess the relationship and effect between independent and dependent variables. To ensure that the stated objectives are met, a 7 point Likert scale questionnaires were administered to 140 managers and non-manager employees. However, only 128 of the questionnaires were returned without errors and ready to go through the analysis processes. Data analysis was conducted in two phases namely the descriptive and inferential statistics. Descriptive analysis aided by the mean counts was applied in describing the empirical data; whereas the inferential statistics of Pearson’s chi-square test and ANOVA were utilized to determine the relationship and the effect of independent on the dependent variable. ANOVA was used to assess the effect of independent variables on the dependent variable. This empirical study demonstrates mix results through Pearson’s chi-square and ANOVA tests. WEP and employee status does not differ from EJS whereas employee position differs from EJS. The ANOVA test revealed a significant effect of WEP and EPS on EJS. The study revealed that SME owners in FB district municipality experienced very high entrepreneurial challenges in contrast to their counterparts in JTG district municipality. Given these findings, the author called on policymakers to prepare specific strategies and programs that motivate employees within the establishment.